Pertumbuhan dan Hasil Pakcoy (Brassica campestris var. chinensis) Pada Berbagai Jenis Nutrisi dan Konsentrasi Pupuk Daun dengan Sistem Hidroponik NFT - Indria Fatika; Rizka Novi Sesanti; Raida Kartina; Sismanto Sismanto; Ratih Rahhutami; Dede Tiara (Politeknik Negeri Lampung, 2023)
One of the keys to successful pakcoy hydroponic cultivation is nutrition. In addition to AB Mix nutrients, sources of nutrients from single fertilizers, compound fertilizers, and foliar fertilizers can also be used as hydroponic nutrition alternatives. The purpose of this study was to determine the interaction of nutrient treatment and foliar fertilizer concentration, to obtain the best type of nutrition, and to obtain the best concentration of foliar fertilizer on growth and yield of pakcoy with the NFT hydroponic system. This research was carried out in greenhouse of Polihidro Farm, Lampung State Polytechnic in June-August 2022. This research used Split Plot Randomized Block Design with the main plot, namely type of nutritions consist of AB Mix 10 ml.l-1 (N1) nutrients, NPK 16 - 16 – 16 2.5 g.l-1 (N2), and nutrients ZA : TSP : KCl (1 g.l-1 : 0.5 g.l-1 : 0.5 g.l-1 ) (N3). Subplots namely foliar fertilizer concentration consist of 0.5 g.l-1 (P1), 1 g.l-1 (P2), 1.5 g.l-1 (P3), 2 g.l-1 (P4), 2.5 g.l-1 (P5), and 3 g.l -1 (P6). The results showed that there was no interaction between type of nutrient and concentration of foliar fertilizer. AB Mix Nutrition 10 ml.l-1 provides the best growth and yield for pakcoy plants. The concentration of foliar fertilizer had no significant effect on growth and yield of pakcoy.